Magnetic resonance imaging guidance for the optimization of ventricular tachycardia ablation. Issue 11 (23rd March 2018) - Mukherjee, Rahul K; Whitaker, John; Williams, Steven E; Razavi, Reza; O'Neill, Mark D
Abstract: Catheter ablation has an important role in the management of patients with ventricular tachycardia (VT) but is limited by modest long-term success rates. Magnetic resonance imaging (MRI) can provide valuable anatomic and functional information as well as potentially improve identification of target sites for ablation. A major limitation of current MRI protocols is the spatial resolution required to identify the areas of tissue responsible for VT but recent developments have led to new strategies which may improve substrate assessment. Potential ways in which detailed information gained from MRI may be utilized during electrophysiology procedures include image integration or performing a procedure under real-time MRI guidance. Image integration allows pre-procedural magnetic resonance (MR) images to be registered with electroanatomical maps to help guide VT ablation and has shown promise in preliminary studies. However, multiple errors can arise during this process due to the registration technique used, changes in ventricular geometry between the time of MRI and the ablation procedure, respiratory and cardiac motion. As isthmus sites may only be a few millimetres wide, reducing these errors may be critical to improve outcomes in VT ablation. Real-time MR-guided intervention has emerged as an alternative solution to address the limitations of pre-acquired imaging to guide ablation. There is now a growing body of literature describing the feasibility, techniques, and potential applications of real-time MR-guided electrophysiology. We review whether real-time MR-guided intervention could be applied in the setting of VT ablation and the potential challenges that need to be overcome.